Synthesis of Zr/La-BTC Bimetallic Metal-Organic Framework (MOF) for Oleic Acid Esterification - Zulys, Agustino; Adawiah, Adawiah; Suminta, Tiara Amalia; Abdullah, Iman; Fadhilla, Rizkha; Nasruddin, Nasruddin; Mabuchi, Takuya (Syarif Hidayatullah State Islamic University, 2024)
Biodiesel plays an essential role in renewable energy as an alternative fuel to tackle the challenges of global warming, environmental degradation, and alternative fossil fuels. Oleic acid can be converted into biodiesel by the esterification process, which employs heterogeneous catalysts such as metal-organic frameworks (MOF). In this study, Zr/La-BTC MOFs were used as different kinds of catalysts to change oleic acid into biodiesel. The characterization results of Zr-BTC, La-BTC, and Zr/La-BTC using FTIR and XRD show that the MOF has been successfully formed. The crystallite sizes for La-BTC, and Zr/La-BTC MOFs are 15.7407 nm and 39.0392 nm, respectively. The surface area of Zr-BTC, La-BTC, and Zr/La-BTC MOFs are 167.101 m2/g, 12.328 m2/g, and 4.764 m2/g. The morphology of Zr-BTC MOF using SEM is irregular, La-BTC is rod-shaped crystal, and Zr/La-BTC is like a knot bond with a narrow waist. The most optimal reaction was obtained at a 5% (w/w) catalyst dosage of total oleic acid and methanol (1:60 mol), 65 °C, and a reaction time of 4 hours, producing 78.11% oleic acid conversion. GC-MS analysis identified that the biodiesel contains oleic acid, palmitic acid, methyl oleate, and methyl palmitate.